Polymeric biomaterials for wound healing - Oliveira, Cristiana; Sousa, Diana; Teixeira, José A.; Ferreira-Santos, Pedro; Botelho, Claudia M. (Frontiers in Bioengineering and Biotechnology, 2023)
Skin indicates a person’s state of health and is so important that it influences a person’s emotional and psychological behavior. In this context, the effective treatment of wounds is a major concern, since several conventional wound healing materials have not been able to provide adequate healing, often leading to scar formation. Hence, the development of innovative biomaterials for wound healing is essential. Natural and synthetic polymers are used extensively for wound dressings and scaffold production. Both natural and synthetic polymers have beneficial properties and limitations, so they are often used in combination to overcome overcome their individual limitations. The use of different polymers in the production of biomaterials has proven to be a promising alternative for the treatment of wounds, as their capacity to accelerate the healing process has been demonstrated in many studies. Thus, this work focuses on describing several currently commercially available solutions used for the management of skin wounds, such as polymeric biomaterials for skin substitutes. New directions, strategies, and innovative technologies for the design of polymeric biomaterials are also addressed, providing solutions for deep burns, personalized care and faster healing.